A case study of facilities management for heritage building revitalisation. Issue 3 (30th September 2019) - Hou, Huiying; Wu, Hao
Abstract : Purpose: Heritage building revitalisation (HBR) is gaining its popularity to intervene historic buildings/sites for their conservation and reuse. Given that multiple stake-holding situations are often involved in HBR process, coordination or managerial problem may hinder versatile facilities design for operational efficiency while preserving the heritage values. To address the coordination challenge, this paper aims to examine the relevance and relative advantages of a FM-led revitalisation strategy for HBR, which the existing literature has not yet addressed. Design/methodology/approach: This paper adopts a case study approach to a major HBR project in Hong Kong. This study conducted field observations and interviews, which were combined with publicly accessible policy and project information to identify stakeholders' opinions and specifications for the role of facilities management (FM) in HBR project process. Findings: The paper reveals the role of FM in coordinating the HBR process for the benefits of stakeholders and general community. FM allows a balanced approach to heritage building adaptation, sound user experience and broader community effects. This enables efficient decision-making, creative facilities design and effective public engagement. FM's strength of fitting in the urban renewal context illustrates its comparative advantage for heritage conservation and revitalisation management. Research limitations/implications: This study develops a conceptual map to identify FM's role in heritage building conservation and revitalisation. This will enhance process evaluation and project decision-making that are central to heritage conservation policy and HBR intervention practices. Originality/value: This study examines relevance and advantage of FM-led business strategy for HBR, which the existing literature has not yet addressed. It discovers FM's strategic roles and initiates a conceptual framework for evaluation of heritage conservation management.